Geospatial Technique Approach to Land Degradation Assessments in Ghana: The Case of the Ejura Sekyedumase District - Allotey, Albert Nii Moe (Annals of Arid Zone, 2019)
This study examined the use of geographic information systems (GIS) as a tool in assessing land degradation caused by water erosion in the Ejura Sekyedumase District, a major food crop production district in Ghana. Data used were land use/cover, slopes/digital elevation models (DEMs) and soil maps. The land use/cover map was derived from Landsat 7 Enhanced Thematic Mapper Plus (ETM+) 2015 satellite imagery. Digital image processing techniques involving image enhancement, manipulation and classification were conducted for land use/cover analysis and images were reclassified with an erosion vulnerability map. A slope map (in degrees) was derived from the DEM. The digital soil map, which was classified according to Food and Agriculture Organization (FAO) groups, was reclassified according to the erodibility classes. The multi-criteria decision module, with a standardized and weighted linear combination approach (WLC) in IDRISI Kilimanjaro was used for the analysis. First, a fuzzy map was created for each map layer, which were later combined to produce a land degradation risk map. The study confirmed that land degradation risks due to erosion exist in the area. Specifically, the southern and central parts of the district were observed as low risk areas (21%), whereas only nine per cent of the area was under high risk. These areas were observed in patches around the southeast, southwest and north-central areas. This study demonstrates that remote sensing (RS) is a major environmental data source which, when integrated with GIS, becomes an effective tool for assessing and mapping land degradation. Key words: Land degradation, Remote Sensing, Geographic Information Systems